The impact of skin allograft on inpatient outcomes in the treatment of major burns 20–50% total body surface area — A propensity score matched analysis using the nationwide inpatient sample. Issue 1 (February 2019) - Sheckter, Clifford C.; Li, Alexander; Pridgen, Brian; Trickey, Amber W.; Karanas, Yvonne; Curtin, Catherine
Abstract: Background: Human cadaveric skin (allograft) is used in treating major burns both as temporizing wound coverage and a means of testing wound bed viability following burn excision. There is limited information on outcomes, and clinicians disagree on indications for application in intermediate-sized burns. This study aims to improve understanding of allograft use in 20–50% total body surface burns by assessing current utilization and evaluating inpatient outcomes. Methods: Discharge data from the Nationwide Inpatient Sample (NIS), Healthcare Cost and Utilization Project (HCUP), Agency for Healthcare Research and Quality assessed 3557 major burn patients (>second degree depth and 20–50% TBSA) undergoing operative treatment. Outcomes were evaluated with propensity score matching. The primary outcome was mortality with secondary outcomes including complications, length of stay, total burn operations, and charges. Results: After matching, 771 allografted patients were paired with 1774 controls. Covariate mean standard differences were all <11% after matching. The average treatment effect (ATE) of allograft on inpatient mortality was an increase of 2.8% (95% CI 0.2–5.3%, p = 0.041). Allograft ATEs were all significantly higher for secondary outcomes: composite complication index increased 0.13 (95% CI 0.07–0.20, p < 0.001), length of stay 8.4 days (95% CI 6.1–1.9 days, p < 0.001), total burn operations 1.6 (95% CI 1.4–1.9, p < 0.001), and total charges 139, 476 [100, 716–178, 236, p < 0.001). Conclusions: Allograft use in major burns 20–50% TBSA was associated with a significant increase in inpatient mortality. There was a notable correlation with increased inpatient complications, longer length of stay, more burn operations, and greater total charges. Better studies are needed to justify the use of this costly and limited resource in the intermediate sized major burn population.